Online Techniques for Dealing with Concept Drift in Process Mining - Carmona, Josep; Gavaldà, Ricard (Advances in Intelligent Data Analysis XI, 2012)
Concept drift is an important concern for any data analysis scenario involving temporally ordered data. In the last decade Process mining arose as a discipline that uses the logs of information systems in order to mine, analyze and enhance the process dimension. There is very little work dealing with concept drift in process mining. In this paper we present the first online mechanism for detecting and managing concept drift, which is based on abstract interpretation and sequential sampling, together with recent learning techniques on data streams.